From manuscript to e-codex. Digitization in Manuscripts Department - Paluszak-Łoś, Maria (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article presents the changes in computer technology and digitization that have taken place in Manuscripts Department, Wrocław University Library, from the beginning of 1990s to date. It describes the contribution of Manuscripts Department to the creation and development of Digital Library of University of Wrocław (DLUWr). It offers the modes of spreading information about manuscripts collections in the Internet via rendering them accessible by digitization and inclusion in Digital Library of University of Wrocław the Department's catalogs and via digital publication of other indexes and registers. The paper also presents the Department's participation in international and Polish projects realized in the Library. The aim of the projects was digitization and Internet access of selected collections of manuscripts via the theme portal 'Cultural Heritage in Wrocław University Library Research' and via Digital Library of University of Wrocław (DLUWr). The article also highlights the significance of digital and digitization endeavors of collections for academic community and sketches their future plans.
Keywords: manuscripts; Cultural Heritage portal; Digital Library of University of Wrocław; Manuscripts Department; manuscript catalogs; projects; Wrocław University Library; digitization